2016
DOI: 10.30699/10.30699/jidai.28.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intracanal Dentin Conditioning with Xylene, Phosphoric Acid and Chlorhexidine on Bond Strength to Glass Fiber Post with Self-Adhesive Cement

Abstract: Background and Aim: Debonding is the most commonly encountered failure in teeth restored with fiber posts that mainly occurs at the weakest interface (dentin-cement interface). Thus, reinforcement of this interface is mandatory. The aim of this study was to evaluate the effect of different root dentin surface treatments after post space preparation on bond strength of fiber posts cemented with a self-adhesive resin cement. Materials and Methods: Forty extracted sound single-rooted teeth underwent root canal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The main characteristics of the 61 selected in vitro studies are presented in Table S2 [10, 11, 15–19, 21–30, 34, 35, 38–78]. Human teeth were used in most of the studies ( n = 40), of which 6 studies used posterior teeth, 31 used anterior teeth, and 24 reported using only single‐rooted teeth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the 61 selected in vitro studies are presented in Table S2 [10, 11, 15–19, 21–30, 34, 35, 38–78]. Human teeth were used in most of the studies ( n = 40), of which 6 studies used posterior teeth, 31 used anterior teeth, and 24 reported using only single‐rooted teeth.…”
Section: Resultsmentioning
confidence: 99%
“…Carbodiimide has shown the capacity to inactivate the catalytic sites of MMPs and cathepsins [34]. Xylene dissolves gutta‐percha and sealer and eliminates the secondary smear layer [35].…”
Section: Introductionmentioning
confidence: 99%